Subthalamic nucleus exclusively evokes dopamine release in the tail of the striatum. Issue 5 (4th August 2022) - Todd, Kathryn L.; Lipski, Janusz; Freestone, Peter S.
Abstract: A distinct population of dopamine neurons in the substantia nigra pars lateralis (SNL) has a unique projection to the most caudolateral (tail) region of the striatum. Here, using two electrochemical techniques to measure basal dopamine and electrically evoked dopamine release in anesthetized rats, we characterized this pathway, and compared it with the 'classic' nigrostriatal pathway from neighboring substantia nigra pars compacta (SNc) dopamine neurons to the dorsolateral striatum. We found that the tail striatum constitutes a distinct dopamine domain compared with the dorsolateral striatum, with consistently lower basal and evoked dopamine, and diverse dopamine release kinetics. Importantly, electrical stimulation of the SNL and SNc evoked dopamine release in entirely separate striatal regions; the tail and dorsolateral striatum, respectively. Furthermore, we showed that stimulation of the subthalamic nucleus (STN) evoked dopamine release exclusively in the tail striatum, likely via the SNL, consistent with previous anatomical evidence of STN afferents to SNL dopamine neurons. Our work identifies the STN as an important modulator of dopamine release in a novel dopamine pathway to the tail striatum, largely independent of the classic nigrostriatal pathway, which necessitates a revision of the basal ganglia circuitry with the STN positioned as a central integrator of striatal information. Abstract : We showed that neurons in the substantia nigra pars lateralis (SNL) constitute a dopamine pathway projecting to the tail of the striatum, a dopamine domain distinct to the dorsolateral striatum which receives input from the substantia nigra pars compacta (SNc). Furthermore, the subthalamic nucleus (STN) exclusively modulates dopamine release in the tail striatum, likely via the SNL. Our work necessitates a revision of the basal ganglia circuitry with the STN positioned as a central integrator of information from both the dorsolateral (motor) and tail (sensory) striatum.